Resting-state functional connectivity for determining outcomes in upper extremity function after stroke: A functional near-infrared spectroscopy study - Sui, Youxin; Kan, Chaojie; Zhu, Shizhe; Zhang, Tianjiao; Wang, Jin; Xu, Sheng; Zhuang, Ren; Shen, Ying; Wang, Tong; Guo, Chuan (Frontiers in Neurology, 2022)
Functional near-infrared spectroscopy(fNIRS) is a non-invasive and promising tool to map the brain functional networks in stroke recovery.Our study was mainly aimed to use fNIRS to detect the different patterns of resting-state functional connectivity (RSFC) in stroke patients with different degrees of upper-extremity motor impairment which defined by FMA-UE. The second aim was to investigate the association between FMA-UE scores and fNIRS-RSFC among different regions of interest(ROIs) in stroke patients. Forty-nine subacute stroke patients were enrolled and were classified into three groups based on FMA-UE scores: mild (n=17), moderate (n=13),and severe (n=19). All patients received 10-minute resting-state fNIRS monitoring. The fNIRS signals were recorded over 7 ROIs: bilateral DLPFC, M1, S1 and middle prefrontal cortex (MPFC).FC was calculated by correlation coefficients between each channels and each ROIs. To reveal the comprehensive differences in FC among three groups, we compared FC at group-level and ROI-level. In addition, to determine the associations between FMA-UE scores and RSFC among different ROIs, Spearman correlation analyses were performed with a significance threshold of p<0.05. For easy comparison, we defined the left hemisphere as the ipsilesional hemisphere. For the group-level comparison,the one-way ANOVA and post-hoc t-tests (mild vs. moderate; mild vs. severe; moderate vs. severe) showed that there was a significant difference among three groups (F=3.42, p=0.04) and the group-averaged FC in the mild group(0.64±0.14) was significantly higher than that in the severe group(0.53±0.14, p=0.013). However, there were no significant differences between the mild and moderate group ( p=0.35) , and between the moderate and severe group (p=0.16). For the ROI-level comparison, the severe group had significantly lower FC of ipsilesional DLPFC-ipsilesional M1 (p=0.015) and ipsilesional DLPFC- contralesional M1 (p=0.035) than those in the mild group. Moreover, Spearman correlation analyses showed that there were significant correlations between FMA-UE scores and FC of the ipsilesional DLPFC-ipsilesional M1(r=0.430, p=0.002), ipsilesional DLPFC-contralesional M1(r=0.388, p=0.006), ipsilesional DLPFC-MPFC(r=0.365, p=0.01) and ipsilesional DLPFC-contralesional DLPFC (r=0.330, p=0.021). The findings indicate that different degrees of poststroke upper-extremity impairment reflect different RSFC patterns, mainly in the connection between DLPFC and bilateral M1. It sheds light on the ipsilesional DLPFC-bilateral M1 as a possible neuromodulation target.